Transforaminal percutaneous endoscopic lumbar discectomy versus microdiscectomy: an Indian rural experience - Chavan, Prakash U.; Gudhe, Mahendra; Munde, Ashok; Jadhav, Balaji (International Journal of Research in Orthopaedics, 2017)
Background: The objective of the study was to compare surgical outcome of micro-discectomy with transforaminal percutaneous endoscopic lumbar discectomy for single level lumbar disc herniation in Indian rural population. Methods: Retrospective comparative study was designed during the period of October 2012 to June 2015, patients in the age group of 22-75 years with unremitting sciatica with/without back pain, and/or a neurological deficit that correlated with appropriate level and side of neural compression as revealed on MRI, with single level lumbar disc herniation who underwent either microdiscectomy or TPELD were included in the study. Patients were assessed on visual analogue scale (VAS) for back and leg pain, modified macnabs criteria, the Oswestry Disability Index (ODI). Results: Group I (MD) included 44 patients and Group II (TPELD) included 20 patients. Significant improvement was seen in claudication symptom post-operatively in both MD and TPELD. Mean operating time was significantly shorter in MD group (1.11 hrs vs. 1.32 hrs; p<0.01). According to modified MacNab’s criteria, outcome were excellent (81.8%), good (9.09%) and fair (9.09%) in MD. Similarly, in TPELD, 80%, 15% and 5% patients had excellent, good and fair outcome respectively. In both groups, no one had a poor outcome. Thus, overall success rate was 100% in the study. Conclusions: TPELD and MD have comparable post-operative outcome in most of the efficacy parameters in Indian rural patients undergoing treatment of single level lumbar disc herniation. Additionally, TPELD offers distinct advantages such as performed under local anaesthesia, preservation of structure, lesser post-operative pain and early mobilization and discharge from hospital.